Ontogeny of cells producing haemolytic antibody or immunocyto-adherance to sheep erythrocytes in the chicken - Solomon, J. B. (1968)
Spleen cell populations producing haemolytic antibody or exhibiting immunocyto-adherence (ICA) to sheep erythrocytes have been studied during ontogeny of the chicken. The proportion of ICA cells in spleens of immunized chickens increased steadily from 1 to 12 weeks of age. In immunized adults, as many as 8 per cent of spleen cells exhibited ICA; this was only ten times the number of similarly active cells in unimmunized adults. In immunized chickens, only a comparatively minor population of spleen cells were engaged in producing haemolytic antibody. There was a sudden increase in plaque-forming cells during 8–10 days after hatching but no further increase in the proportion of such cells during the remainder of development. It is suggested that immunological maturation in the normal animal may be due to cumulative antigenic experience during the first few months of development. Immunological maturation is expressed as an increase in the size of the pool of immunologically competent cells. Increases in population of antibody-forming cells from this pool may occur at different stages in ontogeny according to the type of immunity elicited by antigen.